MODEL PEMBELAJARAN LANGSUNG BERBASIS MEDIA PASIR BERWARNA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP ANGKA 1-10 PADA ANAK AUTISM - MEI ATIKA, PUTRIE (Jurnal Pendidikan Khusus, 2017)
ABSTRACT The purpose of this research was to observe whether there was influence of direct learning model based color sand media toward number 1-10 concept to autism children in SLB Widya Tama Surabaya or not. An autism was a disturbance of pervasive development completely which could disturb the cognitive function, one of them was the understanding of number concept. The direct learning model based color sand media was teaching which was specially designed to support the children’s learning process step by step through color sand media. This research used pre experiment kind. The research design used was obe group pre test post test design. The techniques of data collection were test and documentation.  The data analysis techique was sign test. From the research result it was then analized using sign test formula, and obtained ZH = 2,05 > Zt = 1,96 to significant level 5%. So, it could be concluded that there was influence of direct learning model based color sand media toward understanding ability of number 1-10 concept to autism children in SLB Widya Tama Surabaya.   Keywords: Direct learning, number concept